Intramedullary Fixation for Metacarpal Fractures: A Multi-Institutional Prospective Outcomes Study - Michael B. Gehring, MD; Brandon Wolfe, BA; Riley Kahan, BS; Stephanie D. Malliaris, MD; Kia M. Washington, MD; Matthew D. Folchert, MD; Kyros Ipaktchi, MD; Mark A. Greyson, MD; Alexander Lauder, MD; Matthew L. Iorio, MD (Journal of Hand Surgery Global Online)
Purpose: Intramedullary fixation (IMF) has emerged as an effective treatment for metacarpal fractures. Benefits include stable fixation that allows early postoperative rehabilitation and high fracture union rates, without increased complications. Both headless compression screws and intramedullary threaded noncompressive nails have been described for this purpose; however, prospective outcomes reporting are lacking. This study assessed the outcomes of metacarpal fractures treated with IMF including patient-reported outcomes, grip strength, total active motion, and complications. Methods: A prospective multicenter trial enrolled consecutive patients with closed, extra-articular metacarpal fractures treated with IMF. Radiographic healing was assessed at each postoperative visit and patient-reported outcomes included pain scores, QuickDASH (Disabilities of the Arm, Shoulder, and Hand), and Short Form Survey scores. Grip strength, goniometric motion measurements, and complications were also obtained. Results: One-hundred-one fractures were treated in 82 patients with an average age of 33 years and mean follow-up of 69 days. Most patients were male (70%), nonlaborers (72%), and nonsmokers (74%). QuickDASH scores improved by 40 points, with a final mean of 17 following metacarpal IMF. Short Form Survey components of physical component score and mental component score at final follow-up were 55.95 and 48.74, respectively. Final average grip strength was 15 kg and total active motion was 228º. The average total active motion of the closed reduction cohort (249°) was significantly higher than the open cohort (210°) at final follow-up (P < 0.05). Four complications (3.9%) occurred, including one hardware failure, two proximal screw migrations, and one metacarpophalangeal joint contracture, with three of these patients requiring revision surgery. Conclusions: Intramedullary fixation is a reliable technique for treatment of extra-articular metacarpal fractures with satisfactory patient-reported outcomes, excellent strength and motion, and a low complication rate. Intramedullary fixation should be considered for closed, extra-articular metacarpal fractures. Type of study/level of evidence: Therapeutic IV.